Blood Lead Level of Children and its Trend in Mitrovica, Kosova - Shabani, Driton; Murtezani, Ardiana; Tahirbegolli, Bernard; Bozalija, Adnan; Alili-Idrizi, Edita; Ibraimi, Zana (Journal of Child Science, 2019)
Environmental exposure to lead is considered to be one of the most important hazards to the health of children. Most commonly exposed are those who are poor and live in developing countries. The environmental lead pollution problem in the Roma Mahala neighborhood of Mitrovica was discovered through the appearance of high blood lead levels (BLLs) in children living there. The aim of our study was to investigate the BLLs in children according to gender, age, and area of residence. This study describes the results from a 7-year retrospective study (January 2010–April 2017) based on BLLs conducted on children aged 0 to 13 years living in all three districts of Mitrovica. The survey included 331 children. Blood lead analysis was performed in the laboratory using capillary and venipuncture samples tested by anodic stripping voltammetry using LeadCare II machines. Mean BLLs were the highest in the Roma Mahala with 23.6 mg/dL (standard deviation ± 15.9 µg/dL). We obtained a statistical significance (p < 0.0001) between BLLs according to the settlements. The mean BLLs was higher in the 3 to 4 years aged children group in comparison with other age groups (p = 0.009). In none of the age groups with the Mann–Whitney test we obtained a significant gender difference on BLL (p > 0.05). Lead poisoning levels continue to be a serious problem among children living in Mitrovica over the past several years due to heavy lead pollution. All children from this region should receive environmental evaluations and medical examinations.
Keywords: blood lead levels; children; lead mining and smelting